KSHV/HHV-8 associated lymph node based lymphomas in HIV seronegative subjects. Report of two cases with anaplastic large cell morphology and plasmablastic immunophenotype. Issue 10 (27th September 2005) - Carbone, A; Gloghini, A; Vaccher, E; Marchetti, G; Gaidano, G; Tirelli, U
Abstract : Background: Kaposi sarcoma associated herpesvirus (KSHV)/human herpesvirus 8 (HHV-8) associated lymphomas, which often develop in human immunodeficiency virus (HIV) infected patients with advanced AIDS, present predominantly as primary effusion lymphoma (PEL) or, less frequently, as "solid" extracavitary based lymphomas, associated with serous effusions. These last lymphomas, also called "solid PEL", have been reported before the development of an effusion lymphoma and after resolution of PEL. Interestingly, KSHV/HHV-8 associated lymphomas that present as solid or extracavitary based lesions in HIV seropositive patients without serous effusions have been reported recently. Methods/Results: This paper provides evidence for the existence of a previously undescribed KSHV/HHV-8 associated lymphoma in HIV seronegative patients without serous effusions. These lymphomas exhibit a predilection for the lymph nodes and display anaplastic large cell morphology. These tumours were completely devoid of common cell type specific antigens, including epithelial and melanocytic cell markers. B and T cell associated antigens and other commonly used lymphoid markers were absent or weakly demonstrable in a fraction of the tumour cells. Conversely, immunohistochemical studies showed strong immunostaining with plasma cell reactive antibodies. Conclusions: Analysis of viral infection and immunohistological studies are of primary importance to define this lymph node based KSHV/HHV-8 associated lymphoma with anaplastic large cell morphology and plasmablastic immunophenotype occurring in HIV seronegative patients without serous effusions.